2019–2020 Citrus Pest Management Guide: Crop Insurance Policies Available to Citrus Growers - Ariel Singerman (EDIS)
This 5-page fact sheet is part of the 2019–2020 Citrus Pest Management Guide. It describes the main crop insurance policies available to citrus growers and provides examples that illustrate the calculations involved. Some policies offer coverage for trees, others for production, and others for farm revenue. However, the commonality among all policies is that by purchasing crop insurance, the grower transfers part of the risk in exchange for a premium (the cost of purchasing insurance). Written by Ariel Singerman and published by the Food and Resource Economics Department, March 2019.